A single emitting layer white OLED based on exciplex interface emission. Issue 17 (14th April 2016) - Angioni, E.; Chapran, M.; Ivaniuk, K.; Kostiv, N.; Cherpak, V.; Stakhira, P.; Lazauskas, A.; Tamulevičius, S.; Volyniuk, D.; Findlay, N. J.; Tuttle, T.; Grazulevicius, J. V.; et al.
Abstract : A new triaryl molecule based on a benzene–benzothiadiazole–benzene core has been applied in a WOLED device. Abstract : A new triaryl molecule based on a benzene–benzothiadiazole–benzene core has been applied in a WOLED device. This very simple molecule emits from a combination of emissive states (exciton/electromer/exciplex/electroplex) to give white light with CIE coordinates of (0.38, 0.45) and a colour temperature of 4500 K.